Digitalisation and (de)centralisation in Germany - a comparative study of retail banking and the energy sector - Franz Flögel; Marius Beckamp (Institut Arbeit und Technik (IAT), 2020)
The paper in hand compares retail banking and the electric energy sector to investigate how digitalisation influences (de)centralisation. Structural similarities of both industries like the direct competition of large international companies (Deutsche Bank and RWE) with locale providers such as savings banks and municipal utilities (Stadtwerke) motivate this comparison. Our findings suggest that digitalisation affects (de)centralisation differently. Despite scale economies inherent to processes of digitalisation, small entities must not be on the losing side. Cooperation tends to play a key role for regional companies to profit from digitalisation. Interestingly, digitalisation of the first and second transformation affects (de)centralisation of both industries diametrically (though, it is too early for final conclusions about the second digital transformation). The geographical properties of the businesses in question (i.e. the distance dependence of soft information respectively the physical properties of electricity transmission) and (regulatory) context factors tend to influence the relationship between digitalisation and (de)centralisation. More research is needed to enhance our understanding of digitalisation on (de)centralisation of the economy. As this discussion paper indicates, sector comparisons tend to be useful to contribute to such an understanding.
Keywords: 330; (de)centralisation; digitalisation; energy transition; retail banking; FinTech; EnergyTech; Digital Transformation